2004
DOI: 10.1111/j.1540-8159.2004.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

New Onset of Pacemaker Dependency After Permanent Pacemaker Implantation

Abstract: Pacemaker dependency has dangerous consequences under conditions of electromagnetic interference, unrecognized lead dysfunction, and battery depletion, and has been associated with cardiovascular and overall mortality. The aim of this study was to examine the incidence of new onset of pacemaker dependency during long-term follow-up after pacing system implantation. The study included 518 patients (mean age 72.9 +/- 10.4 years) who presented with intrinsic rhythms at the time of implantation. Indications for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 12 publications
6
27
0
Order By: Relevance
“…In our study, PM dependency was found in 43.5% of the cases, similar to what has been reported in the human literature, where the time of onset is approximately 3 years …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, PM dependency was found in 43.5% of the cases, similar to what has been reported in the human literature, where the time of onset is approximately 3 years …”
Section: Discussionsupporting
confidence: 91%
“…[45][46][47] In our study, PM dependency was found in 43.5% of the cases, similar to what has been reported in the human literature, where the time of onset is approximately 3 years. 24,26,48 Limitations of this study include its retrospective nature, which influenced particularly the timing of re-evaluation: T1 and T2 were homogeneous whereas T3 and T4 had wider CI. Intrinsic rhythm was evaluated during a limited time frame, and for this reason paroxysmal AVB could not be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard electrocardiography was assessed in the VVI mode with a backup frequency of 30 beats/minute. Patients were defined as pacemaker dependent if the intrinsic ventricular rate was less than 30 beats/minute over 30 s, consistent with previous studies …”
Section: Methodsmentioning
confidence: 83%